Comparative Productivity and Profitability of Banana Intercropping with Vegetables: Banana-Vegetable Intercropping Benefits - Shastri, Harsh; Trivedi, Vandana; Thakker, Manish (SAARC Journal of Agriculture, 2025)
Productivity and profitability of vegetables intercropping in banana-based cropping system was analyzed in farmer’s field of MLT site, Madhupur, Tangail in two consecutive years during 2020-21 and 2021-22 to find out a suitable intercrop combination of vegetables with banana for higher productivity and profitability. There were three intercrop-based treatments i.e., Banana + Potato, Banana +Cabbage+ Potato and Banana + Cauliflower + Potato along with Sole banana. Banana (Amrit Sagar), Cabbage (Parel), Cauliflower (Thirty-three) and Potato (Granola) were used as test materials. The experiment was laid out in a randomized complete block design with six dispersed replications. The unit plot size was 400 m2. The results revealed that all the intercrops’ treatments produced higher banana equivalent yield over the sole banana. However, among the intercrop combinations, Banana + Cauliflower + Potato provided the highest equivalent yield (101.89 tha-1 followed by Banana + cabbage + potato. Sole banana produced the lowest equivalent yield in both the cropping seasons. Higher gross margin (Tk.6,66,898 ha-1) was also obtained from Banana + cauliflower + Potato treatment as well as higher BCR (3.79) than other intercrop treatments. So, the farmers of Madhupur Tracts (AEZ-28) and similar areas of Bangladesh could be suggested to cultivated cauliflower and potato as intercrop with banana instead of sole banana. SAARC J. Agric., 22(2): 43-53 (2024)